The effect of art therapy on quality of life and fatigue in breast cancer patients: a meta-analysis - Yujing Zou; Shanshan Zhai; Jiawen Dong; Tianyu Zhao; Jin Yang (Frontiers in Oncology)
Breast cancer imposes a substantial global health burden, with survivors frequently experiencing post-treatment quality of life deficits and chronic fatigue. While art therapy has gained recognition as a potential adjuvant intervention, its therapeutic value remains debated. To evaluate art therapy’s efficacy, we conducted an exhaustive search of major electronic databases through October 2023, identifying 22 eligible RCTs reported in 22 papers that met predefined inclusion criteria from major databases including Web of Science Core Collection, Cochare, Embase, and Pubmed. Study quality was assessed using Cochrane risk-of-bias tools, with data extraction and analysis performed in RevMan 5.3. In this meta-analysis, we aimed to investigate the effect of art therapy on quality of life and fatigue in breast cancer patients. As of October 2023, relevant randomized controlled studies were searched from relevant electronic databases and articles were screened, quality evaluated, and data related to quality of life and fatigue were extracted and analysed using RevMan 5. 3. A total of 22 randomized controlled studies from 22 papers were included in this analysis. The results obtained according to this analysis included the effect of art on quality of life in breast cancer: SMD=0.38 (95% CI, 0.25 to 0.51; P≤0.00001), the fatigue-related indices: SMD=-0.03 (95% CI, -0.21 to 0.15; P=0.73). The effect of intervention time less than two months: SMD=0.21 (95% CI, -0.01 to 0.43; P=0.07), more than or equal to two months: SMD=0.45 (95% CI, 0.28 to 0.62; P<0.00001). Different types of interventions: art therapy in painting and calligraphy: SMD=0.09 (95% CI, -0.17 to 0.35; P=0.49), music-included art therapy: SMD=0.51 (95% CI, 0.32 to 0.70, P<0.00001), music-out-of-treatment art therapy: SMD=0.44 (95% CI, 0.19 to 0.69; P=0.0005). Follow-up time greater than or equal to six months: SMD=0.14 (95% CI, -0.09 to 0.36; P=0.22), follow-up time less than six months: SMD=-0.34 (95% CI, -0.64 to -0.04; P=0.03). In summary, this analysis demonstrated that art therapy improved quality of life, but the effects of fatigue reduction only occur within six months, with the degree of the benefits being correlated with the type, length, and timing of the intervention.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42023476055.